POLITICAL COMMUNICATION STRATEGIES IN THE DIGITAL ERA - Ahmad Sampurna Rambe; Rara Ardina Khairi; Rashin Salsabila; Amelia Lestari Butar Butar; Risky Azzahra; Shendy Sanjaya (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
In the digital era, political communication has undergone a significant transformation, particularly in campaign strategies that utilize social media. Through this communication approach, political actors deliver messages, build images, and foster public engagement within the digital space. This study employs a literature review method to analyze how political communication adapts within the context of viral campaigns in digital media. The findings reveal that political communication is not merely an instrument for conveying information, but also a strategic tool capable of shaping public opinion, expanding campaign reach, and strengthening political legitimacy. This research offers valuable insights into the relationship between digital communication and political influence in the modern era.